Polyethylene wear and rim fracture in total disc arthroplasty - Kurtz, Steven M.; van Ooij, André; Ross, Raymond; de Waal Malefijt, Jan; Peloza, John; Ciccarelli, Lauren; Villarraga, Marta L. (The spine journal, 2007)
Polyethylene (PE) has been used in total disc replacements (TDRs) in Europe since the 1980s. However, the extent of surface damage of PE, including rim fracture and wear, after long-term implantation remains poorly understood. The purpose of this study was to evaluate the magnitude and rate of PE wear and surface damage in TDRs. TDR components were retrieved from patients undergoing revision TDR surgery and conversion to fusion. Twenty-one implants (SB Charité III; DePuy Spine, Raynham, MA) were analyzed from 18 patients (12 female, 6 male) undergoing TDR revision surgery. The components were implanted between 1.8 and 16.0 years (average: 7.8 years) at L2–L3 (n=1), L3–L4 (n=1), L4–L5 (n=11), and L5–S1 (n=8). They were removed due to pain (in all cases) and were associated with subsidence (n=6), anterior migration (n=2), core dislocation (n=2), lateral subluxation (n=1), wear with wire marker fracture (n=1), end plate loosening (n=2), and osteolysis (n=1). Clinical information was collected from medical records and radiographs. Retrieval analysis included dimensional measurements and assessment of the extent and severity of PE surface damage mechanisms. MicroCT scanning was used to identify the presence of internal cracks in the PE core and to scan the geometry of the retrievals. Light microscopy, coupled with white light interferometry, was used to evaluate the surface damage mechanisms at the dome and rim. The dominant wear mechanism was adhesive/abrasive wear at both the dome and rim. End plate penetration (dome wear) ranged from 0.1 to 0.9 mm (average: 0.3 mm), and was correlated with implantation time (Spearman's rho=0.48, p=.03). There was also evidence of macroscopic rim damage, including radial and transverse cracking, fracture, plastic deformation, and third-body damage. End plate penetration measured at the rims ranged from 0.02 to 0.8 mm (average: 0.3 mm). Cracks in the core were oriented transversely in 11 of 21 implants (52%), and radially around the rim in 11 of 21 implants (52%). Radiographic wire marker fracture, observed in 9 of 21 implants (43%), was always associated with deformation, cracking, or fracture of the PE rim. In two cases, a fractured wire marker became lodged in the articulating surface between the PE and the metallic end plate. This is the first study to quantitatively analyze the long-term PE damage mechanisms in contemporary TDRs. The TDRs displayed surface damage observed previously in both hip and knee replacements. Because of the evidence of increasing wear with implantation time, along with the demonstrated potential for osteolysis in the spine, regular long-term follow-up for patients undergoing TDRs is warranted.